Mobilizing Institutional Investments into Emerging Market Infrastructure - Mapila, Kopo (International Finance Corporation, Washington, DC, 2018)
The infrastructure financing gap remains a critical global challenge for sustainable development. New thinking and innovative financial models are needed in order to mobilize more private capital to infrastructure investments. International Finance Corporation’s (IFC’s) new managed co-lending portfolio program for infrastructure seeks to address numerous infrastructure financing challenges that inhibit the flow of resources to emerging markets. The program provides an innovative model for mobilizing financing for infrastructure projects that combines financing from insurance companies, project origination and credit enhancement from IFC, and support from public sector donors.